Canted antiferromagnetism - Morrish, Allan H (Word Scientific, 1994)
Includes bibliographical references (pages 157-173) and indexes.; Hematite (Î±-Fe2O3), the stable oxide of iron, is a major constituent of soils, rocks and the earth's crust. It has unique magnetic properties that make it the prototype for the class of materials known as canted antiferromagnets.This book has no equivalent. The mean-field theory is treated in detail, and thus the book is a useful text for students mastering this general method. Information obtained by a wide variety of experimental methods is provided. These techniques include x-ray and neutron diffraction; electron magnetic resonance; MÃ¶ssbauer spectroscopy; and thermal, optical, electrical and elastic measurements